Implementasi Kebijakan E-Government Pada Pendaftaran Surat Pengantar Nikah Online Di Kelurahan Wonokusumo Surabaya - Indah, Retno Linangkung; Mustofa, Amirul (Soetomo Magister Ilmu Administrasi, 2023)
This study aims to determine the implementation of the online marriage cover letter registration policy through the Surabaya Single Window (SSW) Alfa application in Wonokusumo Village, Surabaya along with its supporting and inhibiting factors. This research is a type of qualitative research with a descriptive approach. The research used the theory of policy implementation according to George Edward III, with 4 focuses, namely communication, resources, disposition and bureaucratic structure. The collection of research data was carried out through observation, interviews, document studies. The data analysis used is data collection, data condensation, data presentation and drawing conclusions. The results of the study found that the implementation of the SSWAlfa Policy in general for the four focus of policy implementation, namely the focus of communication, resources, disposition and bureaucratic structure has been positively supportive, so that the policy was successfully implemented well, although there were several obstacles that could be overcome. Factors supporting the implementation, are a) the existence of parties who can cooperate with the Village in policy outreach activities, namely the RT, RW, LPMK and KSH (Surabaya Great Cadres) offline at Balai RW; .b) the existence of Instagram online media that can be utilized in disseminating policies; c) the availability of reliable human resources for the Wonokusumo Village service staff who are serious about implementing policies; d) there is already a routine budget for all public services in the Wonokusumo Village office; e) the existence of routine facilities, facilities and infrastructure that are used for all public services at the Wonokusumo Village office; f) the seriousness of the RT and RW officials in verifying the application for a marriage introduction online through the ‘Sayang Warga’ application; e) there is a bureaucratic structure for the Wonokusumo Village that can be used to implement policies so that there is clear division of labor in implementing the policy. Meanwhile, the inhibiting factors are: a) there are still some aplicants who do not understand information technology; b) there are still RTs, RWs and applicants who are not aware of the new regulations regarding registration of marriage cover letters which must be done online; c) there are still RTs and RWs who don’t know how to verify applications via the ‘Sayang Warga’ application; d) there are still some applicants who do not understand digital technology. Finally,the researcher compiled recommendations, namely that the Wonokusumo Village should further intensify offline and online socialization on the use of socialization of the use on SSWAlfa in arranging Marriage Certificates online, form several assistance cadres at the RW level to help applicants who still don’t understand how to access the SSWAlfa application, and the Wonokusumo Village should further intensify training for RT and RW administrators who have not been able to verify the applicants. Keywords: Policy Implementation, Online Marriage Certificate Registration, SSWAlfa Application